Grain yield, dry matter remobilization and chlorophyll content in maize (Zea mays L.) as influenced by nitrogen and water deficit (Bangladesh Journal of Botany, 2018)
Out of 20, 40, 60 and 80 per cent moisture depletion 20% showed significantly higher grain yields, biological yield, chlorophyll a, b than the others. However, the highest contribution of stem and leaf dry matter remobilization in grain yield were obtained in 80% moisture depletion and 300 kg N/ha and the lowest one was found in the 20% moisture depletion and 150 kg N/ha. Nitrogen application increased all traits, however there were no significant difference between 250 and 300 kg N/ha.